Evolving disaster governance paradigms in Nepal. (November 2020) - Vij, Sumit; Russell, Caroline; Clark, Julian; Parajuli, Binod Prasad; Shakya, Puja; Dewulf, Art
Abstract: This article aims to explain various disaster governance paradigms that have emerged and currently exists in Nepal. A disaster governance paradigm is a comprehensive set of prevailing and institutionalized ideas that shape disaster plans and policies that eventually are implemented on-the-ground. Nepal has prepared various disaster plans and policies at the national, provincial and local level, but there are major gaps in disaster risk preparedness, with annual floods and landslides continuing to be responsible for the loss of lives and heavy infrastructure damages. In this article, we show how disaster governance paradigms have evolved between 1982 and 2019, using policy document analysis and semi-structured interviews with key policy actors. The study found that four major disaster governance paradigms exist in Nepal – (1) response and recovery; (2) disaster risk reduction and management; (3) integrated climate change adaptation and disaster risk reduction; and (4) federalized disaster risk reduction. The results of this study show that multiple state and non-state actors such as key government ministries, NGOs, INGOs and other civil society actors are competing over resources and there is an ongoing administrative struggle for promoting different disaster governance paradigms. There has been a push from various civil society actors to prioritize disaster risk reduction in Nepal. Finally, we conclude that it is too early to assert that the decentralization process will be able to reduce disaster risk for vulnerable communities, especially with the federalization of Nepal's disaster governance.